Screening for Spiritual Suffering by Nurses - Bahraini, Sayna (Université d'Ottawa / University of Ottawa, 2020)
Purpose: To contribute to improved screening of patients for spiritual suffering and subsequently referring to specialized spiritual care services at an urban complex continuing care hospital in Ottawa, Canada. Methods: I conducted a series of studies using different methods including:1) A systematic review to synthesize the evidence regarding the accuracy of measures to screen adults for spiritual suffering, 2) a qualitative study to iteratively select a measure to screen patients for spiritual suffering and simultaneously plan for its implementation, and 3) A diagnostic test accuracy study protocol that examines the accuracy of the selected screening measure in a complex continuing care hospital. Findings: In the systematic review, we identified five articles that provided information on 24 spiritual screening measures and their diagnostic accuracy criteria. The methodological quality of all included studies was low. Healthcare providers in the focus group interviews specified eight considerations they believed were important for selecting a spiritual screening measure. Among 24 identified measures in the systematic review, they selected the Peace and Meaning/Joy as the measure that best met these considerations. Healthcare providers and patients determined the implementation process of the selected screening measure for their hospital. Participants in my study believed that nurses need special training to use the selected screening measure. Conclusion: Driven by demands to integrate spiritual care into routine patient care, this research identified evidence-based spiritual measures, contributed to the development of a plan to implement a spiritual suffering screening measure, and development a methodologically rigorous protocol to examine the accuracy of the selected screening measure. Findings from this doctoral thesis provide information about strategies of screening that can be considered an essential step toward addressing some of the clinical issues and research priorities surrounding identifying patients with spiritual suffering, however, there is much work to be done.
Keywords: spiritual suffering; screening; qualitative study; systematic review; diagnostic test accuracy; nursing